Strong Influence of Pressure on the Magnetic Properties of MgB2 Bulk Superconductors - Burcu Savaşkan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2023)
The influence of the pressure on the magnetic and superconducting properties of polycrystalline MgB2 bulks was studied. Bulk MgB2 samples were prepared using conventional in-situ solid state reaction and hot-pressing methods. The structural and electromagnetic properties of MgB2 samples were studied by using x-ray diffraction (XRD), scanning electronic microscope (SEM), magnetic hysteresis (M-H) and magnetic levitation force (Fz, Fx) measurements. XRD measurements proved high quality of MgB2 bulks with only small traces of MgO impurity phase. The zero-field Jc value reached 240 kA/cm2 for MgB2 sample produced by hot-press while 23 kA/cm2 for MgB2 sample produced by conventional in-situ at measurement temperature of 25 K. The max. levitation force values were obtained as 11.60 N and 15.42 N for MgB2 bulk samples produced by in-situ and hot-press methods at 25 K, respectively. All these magnetic measurements result indicate that pressure acts like driving force for manufacturing highly dense and high levitation capability MgB2 bulk superconductors.